Evaluating the Validity and Reliability of the Reflective Practice Questionnaire for Assessing Reflective Capacity among Medical Students in Central India - Dhurandhar, Diwakar; Pathak, Swanand; Chandrakar, Tripti; Singh, Adarshlata; Anjankar, Vaibhav; Agrawal, Jagriti (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Reflection or metacognition can be described as the process of contemplating one's own thinking. It facilitates the cultivation of profound learning and critical thinking skills. Reflective Practice Questionnaire (RPQ) validation study has been conducted among Medical Students studying in American University. Its validity and reliability has not been sufficiently tested among Indian medical students so far. This study aimed to assess the validity, reliability, and factor loadings of RPQ among 171 final-year students from the Competency-Based Medical Education (CBME) batch and 129 interns from the Non-CBME batch at a medical college in central India. Materials and Methods: The present cross-sectional descriptive study was conducted by self-administered RPQ consisting of 10 subscales and 40 items. Questionnaire was evaluated for validity by using Table of critical values for Pearson’s r. Reliability was estimated using Chronbach’s alpha with value less than 0.6 not acceptable. Factor Analysis of Reflective Capacity subscale was conducted by Principal Factor Method. Results: Response rate of 90% was achieved with total 300 medical students participating after giving consent. All the items of RPQ passed the test of validity except 4 items. Only Job Satisfaction (JS) subscale had less than 0.6 Chronbach’s alpha value, thus was not found to be a reliable subscale. All the factors of Reflective Capacity subscale had communalities or Factor loadings of more than 0.3 which is acceptable value of any factor. Discussion: RPQ must be modified according to findings of the present study. The difference in Sociocultural setting and a myriad of other aspects may make a significant difference in applicability of a questionnaire in a new population setting.
Keywords: Reflective Practice Questionnaire; Validity; Reliability; Factor loadings; Reflection; Medical students